2016
DOI: 10.1038/bjc.2015.467
|View full text |Cite
|
Sign up to set email alerts
|

Serum lactate dehydrogenase as an early marker for outcome in patients treated with anti-PD-1 therapy in metastatic melanoma

Abstract: Background:Treatment with programmed death receptor-1 (PD-1) antibodies is associated with high response rates in patients with advanced melanoma. Reliable markers for early response and outcome are still sparse.Methods:We evaluated 66 consecutive patients with advanced/metastatic melanoma treated with nivolumab or pembrolizumab between 2013 and 2014. The main objectives of this study were to investigate whether, first, serum lactate dehydrogenase (LDH) at baseline (normal vs above the upper limit of normal) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
197
1
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 272 publications
(219 citation statements)
references
References 30 publications
18
197
1
3
Order By: Relevance
“…As previously described, several potential biomarkers for nivolumab have been suggested in recent years [518]. As to routinely-obtained clinical findings, only cutaneous AEs and LDH have been reported [17, 18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As previously described, several potential biomarkers for nivolumab have been suggested in recent years [518]. As to routinely-obtained clinical findings, only cutaneous AEs and LDH have been reported [17, 18].…”
Section: Discussionmentioning
confidence: 99%
“…However, these biomarkers are not entirely reliable and their investigation is labor-intensive and thus impractical in daily clinical practice. On the other hand, predictors which are also routinely obtained clinical findings, such as serum lactate dehydrogenase (LDH) and cutaneous adverse events (AEs), have only been assessed by a small number of investigators [17, 18]. …”
Section: Introductionmentioning
confidence: 99%
“…In 80% (12/15) of patients with no response, the baseline levels of CD45RO + /CD8 + T cells were ≤25%, whereas all (6/6) patients with a response had ≥30% CD45RO + /CD8 + T cells 81 . In addition, elevated pretreatment levels of LDH were shown to be negatively associated with overall survival in patients with melanoma treated with ipilimumab or pembrolizumab 7678,82,83 .…”
Section: Biomarkers Of Immunotherapy Responsementioning
confidence: 99%
“…An independent study showed that low baseline serum LDH is associated with favorable outcome of latestage melanoma patients treated with ipilimumab and, therefore, confirmed that baseline serum LDH is a strong marker for prognosis in advanced melanoma (11). The suitability of serum LDH as a predictive factor was also demonstrated for therapy with further immunomodulatory drugs, anti-programmed death receptor-1 (anti-PD-1) antibodies pembrolizumab and nivolumab (12). The authors documented that anti-PD-1-treated patients with a relative reduction of serum LDH compared with their baseline LDH achieved partial remission.…”
Section: Biomarkers In Malignant Melanoma: a Current Statusmentioning
confidence: 86%